Boosting Productivity through Recruitment, Motivation, and Training in Indonesia: Meningkatkan Produktivitas melalui Rekrutmen, Motivasi, dan Pelatihan di Indonesia - Kiki amelia; Lilik Indayani (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the impact of recruitment, work motivation, and job training on employee productivity at PT. Sinar Bima Sakti. Utilizing a quantitative, descriptive approach, data were gathered from 71 employees through accidental sampling and analyzed using SPSS Version 2022. Results show that all three factors positively and significantly influence productivity, explaining 66.1% of its variance. The study suggests that improving recruitment practices, maintaining effective motivation strategies, and optimizing job training can significantly enhance employee productivity. Highlights: 1. Positive Impact: Recruitment, motivation, and training boost employee productivity. 2. Significant Contribution: Factors explain 66.1% of productivity variance. 3. Improvement Needed: Enhance recruitment, maintain motivation, optimize training. Keywords: recruitment, work motivation, job training, employee productivity, quantitative analysis